Strategy focused instruction in literacy education and second language learning for adults (LESLLA) in the Netherlands - Dalderop, Kaatje; Andringa, Sible; Rispens, Judith (Dutch Journal of Applied Linguistics, 2023)
This survey study focused on the strategies that LESLLA teachers in the Netherlands model and train in their classes. A questionnaire was developed aiming at tapping into four different strategy types: metacognitive, social, affective and cognitive strategies. Eighty two LESLLA teachers participated in the study. The study revealed remarkable differences between teachers: 17% of the respondents could be characterized as strongly strategy focused, whereas 41% of the participants was categorized as strategy focused and 32% as moderately strategy focused. 10% of the teachers reported to rarely focus on any strategy at all. The results showed that the teachers in our sample focused more frequently on metacognitive and social strategies and less on affective and cognitive strategies. Strategy focus could not be related to teacher characteristics, such as their training or their years of teaching experience, and also not to the proficiency level of their learners.